Experimental investigation on aging characteristics of asphalt based on rheological properties. (20th January 2020) - Wang, Ze; Ye, Fen
Highlights: The types of asphalt selected in the test cover five of the most representative asphalts in China, 70#, 90# base asphalts and three kinds of modified asphalts. SHRP index and conventional indexes are combined to characterize the aging characteristics of asphalt by material rheology. Multi-Stress Creep and Recovery was considered to analyze the aging characteristics. Pearson correlation analysis between five indexes of rheological properties and penetration and softening point was carried out, to study the aging characteristics of asphalt. Abstract: Along with the concept of long-life asphalt pavement design, requirements for durability is increasing. As a kind of viscoelastic organic material, asphalt aging performance is closely related to rheological properties. Base asphalt from different sources and 3 modified binders were selected. Short-term and long-term laboratory aging were performed to simulate actual aging. The penetration and softening point of asphalt at different aging levels were tested. Asphalt binder rheological properties tests were also conducted to study rheological properties indexes such as rutting factor(G*/sin δ), phase angle δ, complex modulus G* and elasticity modulus. The results showed that the high-temperature performance was enhanced along with the degree of aging. Unrecoverable creep compliance decreased and percentage of creep recovery increased obviously after aging. The accuracy of the penetration evaluation method would be reduced when penetration index was used to evaluate the performances of aged asphalt. Despite that phase angle could represent the changes during the aging process, it was not suitable for making a comparison about the high-temperature performances among different kinds of aged asphalt binders. Among these 5 binders, 18% rubber modified asphalt has the best high temperature anti-rutting performance and 4.5%SBS takes the second place, and base asphalt has the worst high temperature anti-rutting performance. Through the Pearson correlation analysis between 5 rheological property indexes as mentioned above and penetration and softening point, it could be concluded that the rheological property indexes are in good correlation with softening point but is weakly related with penetration.